The CHALLENGING TRADITIONAL RECRUITMENT METHODS IN MALAYSIA - Elijah Noor Azmi; Adrian Budiman; Che Su Mustafa (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2023)
Whilst there has been many research on the use of traditional method, as well as an increasing amount of interest in the use of job portals in Malaysian recruitment, few studies however have yielded detailed insights of how social networking sites are getting evolved to become one of the highly used method in recruitment. The qualitative study described in this paper aims to explore the views of recruitment methods in Malaysia and to inform the current views on social networking sites as effective recruitment methods. This study uses the Uses and Gratifications Theory (U&G) to enable the researcher to further examine the effectiveness of the U&G theory towards social networking sites, and to relate on how widely people understand their methods of choice as a recruitment tool.